2007
DOI: 10.1126/science.1137975
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solvent-Host Interactions That Lead to Very Large Swelling of Hybrid Frameworks

Abstract: An unusually large expansion upon solvent adsorption occurs without apparent bond breaking in the network of a series of isoreticular chromium(III) or iron(III) diarboxylates labeled MIL-88A to D [dicarbox = fumarate (88A); terephthalate (1,4-BDC) (88B); 2,6-naphthalenedicarboxylate (2,6-NDC) (88C); and 4-4'-biphenyldicarboxylate (4-4'-BPDC) (88D)]. This reversible "breathing" motion was analyzed in terms of cell dimensions (extent of breathing), movements within the framework (mechanism of transformation), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
803
2
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 980 publications
(841 citation statements)
references
References 10 publications
29
803
2
7
Order By: Relevance
“…The crystal structure analysis of ([Cd(tn)] 3 [Cr(CN) 6 ] 2 ) ∞ (2) revealed that it is also a three-dimensional network with both (15) Å, which is usual for six coordinated CdN 6 . 52 Again the structure can be described as being formed of hexametallocycles consisting of only Cd1 atoms and tn ligands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The crystal structure analysis of ([Cd(tn)] 3 [Cr(CN) 6 ] 2 ) ∞ (2) revealed that it is also a three-dimensional network with both (15) Å, which is usual for six coordinated CdN 6 . 52 Again the structure can be described as being formed of hexametallocycles consisting of only Cd1 atoms and tn ligands.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28] Some cyanide-bridged inorganic coordination polymers, prepared by assembling cyanometalate anions and transition metal complexes as building blocks, have also been found to have framework structures. The hexacyanometalates, M II (CN) 6 4-and M III (CN) 6 3-, are good building blocks, and a number of multidimensional systems have been synthesized, some with interesting magnetic properties. [29][30][31][32][33][34] Interest in the gas sorption properties of these compounds has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common approach to synthesize isoreticular MOFs with different pore sizes is to combine metal clusters and organic linkers of various sizes. This has been demonstrated by combining metal clusters with ditopic linkers such as in the IRMOF-n series with tetrameric Zn clusters, 9 the MIL-88 10 and MIL-101 11,12 series with trimetric metal clusters, and the UiO-66 series with hexameric Zr clusters. 13 Isoreticular MOFs have also been synthesized by combining metal clusters with tritopic linkers, such as in the HKUST-1 series with dimeric metal paddle-wheel clusters 14−17 and the MIL-100 series 11,18 with trimeric metal clusters.…”
Section: ■ Introductionmentioning
confidence: 99%